Evaluasi Sistem Penagihan Pembayaran WiFi Berbasis Web dengan Pendekatan Finite State Machine - Nur Abidin; Erwin Choirul Anif (BRILIANT: Jurnal Riset dan Konseptual, 2026)
Web-based WiFi billing management requires consistent invoice status and timely delivery of payment notifications to customers. Frequent problems in billing systems are inconsistent invoice status changes and late notification delivery, which impact the effectiveness of service management and customer satisfaction. This study aims to evaluate the implementation of a Finite State Machine (FSM) in managing invoices and WhatsApp notifications in a web-based WiFi billing application developed using the Laravel framework. The research method used is an evaluative study with a case study approach. The research stages include a literature review, analysis of the existing billing system, evaluation of the FSM flow in managing invoice status, and analysis of the results of the WhatsApp notification implementation. FSM is implemented to manage invoice status transitions from draft, sent, due, paid, to isolated in a structured manner. The evaluation results show that the implementation of FSM can improve the consistency of invoice status management, reduce status transition errors, and improve the accuracy of WhatsApp notification delivery to customers. Thus, FSM is proven effective as a process flow control model in a web-based WiFi billing application.